The role of exercıse ın reducıng the sıde effects of antıpsıcotıcs used ın the treatment of bıpolar dısorders - Hatice Toy; ERKUT Tutkun; ITIR Tarı Cömert (Türk Spor ve Egzersiz Dergisi)
ABSTRACTThe study is a systematic evaluation of quantitative studies showing the relationship between drug use and physical activity in investigating the side effects of antipsychotics used in patients who have bipolar disorder.Bipolar disorder is usually treated with medicine and the side effects of the drugs which are used to increase the body mass index of patients and this causes obesity. This study mainly aims to examine the role of exercise in reducing the side effects of antipsychotics which are used by individuals who have bipolar disorder with using the high-level evidence which was acquired from published systematic reviews and meta-analyzes.Most antipsychotics cause weight gain; olanzapine and clozapine are seen as the antipsychotics which have highest risk. In the first period after taking antipsychotics, the weight is increasing rapidly, and patients continue to gain weight in the long term. One of the best strategies to prevent this situation is to adapt antipsychotics according to individual needs and to check over weight and other metabolic parameters closely.The researches which were done and current information in the last 10 years were included in the study. Recent studies have shown that in the patients who have bipolar disorder, physical activity programs can play a significant role in supporting of mental and physical health. We hope that adding exercise to treatment plans for individuals with bipolar disorder may provide side benefits and be guidance for clinical practice, policy and future research.